2016
DOI: 10.1039/c6cc06344f
|View full text |Cite
|
Sign up to set email alerts
|

NIR absorbing diferrocene-containing meso-cyano-BODIPY with a UV-Vis-NIR spectrum remarkably close to that of magnesium tetracyanotetraferrocenyltetraazaporphyrin

Abstract: Diferrocene-containing meso-cyano-BODIPY (4) was prepared by the direct cyanation/oxidation reaction of symmetric BODIPY 1 followed by Knoevenagel condensation with ferrocenealdehyde. Ferrocene-containing BODIPY 4 was characterized by a variety of spectroscopic, electrochemical, and theoretical methods and its UV-Vis-NIR spectrum has a striking similarity with a UV-Vis-NIR spectrum of the previously reported magnesium 2(3),7(8),12(13),17(18)-tetracyano-3(2),8(7),13(12),18(17)-tetraferrocenyl-5,10,15,20-tetraaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…[8,12,13] BODIPYs with vinylferrocene fragments connected to the BODIPY core at 3-or 3,5-positions have intense lowenergy MLCT bands. These bands dominate the UV-Vis-NIR region in case of the diferrocenyl-containing systems 12-15 (Figure 8), [9,16,25,34] while clear overlap between MLCT transitions and π-π* bands are observed in asymmetric BODIPYs 17 [16] and 19-20 [27] with strong electron-donating N,N-dimethylaminophenyl-or phenoxy-substituents. Diferrocenyl-containing BOPHY chromophore 26 [18] has a very Ferrocenyl-Containing BODIPYs, aza-BODIPYs, BOPHYs, Transition-Metal Dipyrromethenes and aza-Dipyrromethenes [10] 2 DCM 613 (4720), 735 (4680) [10] 3 DCM 313 (21000), 543 (19000), 673 (15000) [22] 4 DCM 310, 535 (10000), 697 (18000) [6] 5 DCM 459 (4380), 628 (4970), 856 (4380) [10] 6 DCM 471 (4370), 680 (5000), 824 (4320) [10] 7 DCM 450 (5000), 623 (15500), 850 (14000) [22] 8 DCM 310, 599 (12500), 837 (25000) [6] 9 Toluene 509 (75857), 656 (5248) [33] 10 Toluene 350, 400, 513 (32300) [26] 11 DCM 245, 280, 350, 498 [32] 12 DCM 340, 550, 700 [34] 13 DCM 358 (17000), 575 (18000), 750 (16000) 645 0.176 [16] 14 DCM 342, 590, 739 (30000) [25] 15 DCM 370 (30000), 420 (26500), 654 (48000), 926 (27000) [9] 16 DCM 369 (18000), 554 (54000), 671 (18000) 595 0.136 [16] 17 DCM 363 (29000), 650 (31000), 750 (40000) 640 0.260 [16] 18 DCM 366 (12000), 613 (48000), 715 (22000) 655 0.260 [16] 19 PhCN 370, 590, 660 [27] 24 DCM 370, 446, 818 (59300) [35] 25 DCM 370, 440, 495, 810 (118000) [35] 26 DCM 343 (28000), 694 (32000) [18] 27 THF 492 (29400) [11] 28 Toluene 350, 400, 523 (32400) 546 0.002 …”
Section: Optical Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…[8,12,13] BODIPYs with vinylferrocene fragments connected to the BODIPY core at 3-or 3,5-positions have intense lowenergy MLCT bands. These bands dominate the UV-Vis-NIR region in case of the diferrocenyl-containing systems 12-15 (Figure 8), [9,16,25,34] while clear overlap between MLCT transitions and π-π* bands are observed in asymmetric BODIPYs 17 [16] and 19-20 [27] with strong electron-donating N,N-dimethylaminophenyl-or phenoxy-substituents. Diferrocenyl-containing BOPHY chromophore 26 [18] has a very Ferrocenyl-Containing BODIPYs, aza-BODIPYs, BOPHYs, Transition-Metal Dipyrromethenes and aza-Dipyrromethenes [10] 2 DCM 613 (4720), 735 (4680) [10] 3 DCM 313 (21000), 543 (19000), 673 (15000) [22] 4 DCM 310, 535 (10000), 697 (18000) [6] 5 DCM 459 (4380), 628 (4970), 856 (4380) [10] 6 DCM 471 (4370), 680 (5000), 824 (4320) [10] 7 DCM 450 (5000), 623 (15500), 850 (14000) [22] 8 DCM 310, 599 (12500), 837 (25000) [6] 9 Toluene 509 (75857), 656 (5248) [33] 10 Toluene 350, 400, 513 (32300) [26] 11 DCM 245, 280, 350, 498 [32] 12 DCM 340, 550, 700 [34] 13 DCM 358 (17000), 575 (18000), 750 (16000) 645 0.176 [16] 14 DCM 342, 590, 739 (30000) [25] 15 DCM 370 (30000), 420 (26500), 654 (48000), 926 (27000) [9] 16 DCM 369 (18000), 554 (54000), 671 (18000) 595 0.136 [16] 17 DCM 363 (29000), 650 (31000), 750 (40000) 640 0.260 [16] 18 DCM 366 (12000), 613 (48000), 715 (22000) 655 0.260 [16] 19 PhCN 370, 590, 660 [27] 24 DCM 370, 446, 818 (59300) [35] 25 DCM 370, 440, 495, 810 (118000) [35] 26 DCM 343 (28000), 694 (32000) [18] 27 THF 492 (29400) [11] 28 Toluene 350, 400, 523 (32400) 546 0.002 …”
Section: Optical Propertiesmentioning
confidence: 99%
“…In the most of case, DFT and TDDFT calculations using standard hybrid (20 % of Hartree-Fock exchange) B3LYP exchange-correlation functional coupled with doubleor triple-ζ quality basis sets provide a good agreement between theoretical and experimental data. [6][7][8][9]11,13,16,19,21,[23][24][25]29,32,35] In several cases of the ferrocenyl-containing azaBODIPYs and BOPHY, however, it was shown that use of the hybrid TPSSh (10 % of Hartree-Fock exchange) results in better correlation between theoretical and experimental data. Modified from reference [6] .…”
Section: N Nemykin Et Almentioning
confidence: 99%
See 3 more Smart Citations